Pengaruh Adiksi Permainan Daring terhadap Disiplin Belajar Siswa Kelas V SDN 002 Samarinda Utara Tahun Pembelajaran 2019/2020 - Widodo, Bekti; Khairunnisa, Ratna (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2020)
The purpose of this study is to find out the effect of effect of online game addiction on the learning discipline of fifth grade students of SDN 002 North Samarinda in Academic Year 2019/2020. This research was conducted at SDN 002 North Samarinda in September 2019. The sampling technique in this study was Saturated Sampling. The subjects in this study were students of class V SDN 002 North Samarinda. This study used questionnaire and documentation as data collection techniques. Data analysis techniques used inferential statistical analysis using the IBM SPSS 20. The normality test results concluded that the residual value was normally distributed by obtaining a significance value = 0.317> significance level = 0.05. Homogeneity test results concluded that the distribution of data is homogeneous, with a significance value = 0.819> significance level = 0.05. Mean test result was Fcount = 23.889>Ftable = 3.99, so, it can be concluded that there is an influence of online game addiction on students’ learning discipline. The amount of influence is determined by the coefficient of determination r2 = 0.274 or by 27.4%.